Chemical and Microbiological Characteristics of Antimicrobial Edible Film (AmEF) from Chicken Bone Waste Gelatin with The Addition of Tea Leaf Extract (Camelia sinensis) - Windyasmara, Ludfia; Afriyanti, Afriyanti; Handayani, Catur Budi; Wardana, Wardana Kusuma (Jurnal Ilmu dan Teknologi Peternakan Tropis, 2022)
ABSTRACTThe edible film is a thin layer that can be produced from edible macromolecules. One of the ingredients for the edible film is gelatin from chicken bone waste which can be obtained from slaughterhouses. The edible film can be combined with other components such as antimicrobial substances found in tea plants. This study aims to determine the effect of variations in heating temperature and the addition of tea extract as an antimicrobial edible film. Research parameters include water content, total phenol, and zone of inhibition. The experimental design used was a factorial completely randomized design with 2 treatment factors, namely X = additional concentration of tea leaf extract 0%, 20%, 25%, 30%, and 35% and Y = variations in heating temperature of 70⸰C and 80⸰C, each treatment was repeated 2 times. The data obtained were analyzed by ANOVA and if there was a significant difference between treatments, it was continued with the DMRT test (Duncan Multiple Range Test). The results of this study indicate that variations in heating temperature have no significant effect on water content, total phenol, and antimicrobial edible film inhibition zone. The highest water content value was 21.12% at a heating temperature of 70⸰C and the tea extract was 30%, the highest total phenol value was 13.01 g GAE/g obtained at 30% tea extract concentration and the highest inhibition zone was at 30% tea extract concentration. with a value of 1.97 cm.Keywords: Antimicrobial edible film, tea extract, gelatin, heating temperature